Prevalence of Intestinal Parasitosis and Its Associated Factors Among Children Aged 6 to 59 months Attending Mekane Eyesus Primary Hospital, Northcentral Ethiopia - Tahir Eyayu; Amilaku Wubie; Teklehaimanot Kiros; Tegenaw Tiruneh; Shewaneh Damtie; Meslo Sema; Aynework Abebaw; Ermias Sisay Chanie; Lemma Workineh (SAGE Publishing, 2021)
Background . Intestinal parasites are still a serious public health problem and important cause of morbidity and mortality all over the world, particularly in developing countries. Unfortunately, pre-school children are more susceptible to infection. However, information is scarce in the study area. Thus, this study aimed to assess the prevalence of intestinal parasitosis and associated factors among children aged 6 to 59 months in Northcentral Ethiopia. Methods. An institutional-based cross-sectional study was carried out at Mekane Eyesus primary hospital from June 10 to November 30, 2020. Stool samples were collected from 322 children and examined by using direct wet mount and formal ether concentration techniques. The data were entered and analyzed using EPI Info v7 and SPSS v23 statistical software, respectively. Both bivariable and multivariable logistic analysis was carried out and potential associated factors were identified based on adjusted odds ratio with 95% confidence interval and P -value <.05. Results. The prevalence of intestinal parasitosis was 18.0% (95% CI: 14.0%-22.0%). A total of 4 parasites were examined and the dominant parasite was E. histolytica /dispar (8.1%) followed by A. limbricoide (4.7%). Children with irregular trimming of fingernails (AOR = 3.14, 95% CI: 1.59-6.21), and child who have habit of eating unwashed fruits/vegetables (AOR = 3.80, 95% CI: 1.14-12.82) were strongly associated with IPIs. Conclusions. Protozoa parasites are most common cause of diseases in children. The study identified some preventable and modifiable factors to address the prevalence of IPIs. Additionally, improving mothers/guardians awareness about source of infection and mode of transmission is necessary.